KONTESTASI OTORITAS KEAGAMAAN DALAM TAFSIR GENDER DI WEBSITE (STUDI MUSLIMAHNEWS.NET DAN BINCANGMUSLIMAH.COM) - Mayasari, Lutfiana Dwi (Center of Gender Studies and Child of State Islamic Institute of Metro, 2024)
One of the widely discussed issues on Islamic websites is gender interpretation, as the gender narrative has been polarized since the inception of this issue. Utilizing qualitative methodology, this research will employ the theory of Muslim public space to analyze the patterns of Islamic media contestation focusing on gender interpretation, namely muslimahnews.net and bincangmuslimah.com. New media theory is utilized to analyze the shift in patterns of religious authority from traditional to impersonal media. The research findings conclude that muslimahnews.net constructs a pattern of religious authority as a populist media with three prominent narratives: the oppression of women due to the regime, a purification narrative calling for women to return to fitrah, and an anti-authoritarian narrative urging women to resist policies contradicting Islamic law. Meanwhile, bincangmuslimah.com constructs a pattern of religious authority as a moderate media that prioritizes values of tolerance, national commitment, and anti-violence by considering equality for men and women as a counter-narrative to narratives oppressing women's authority. The shift in patterns of religious authority from traditional to impersonal media reinforces the polarization of Islamic groups, thus necessitating a joint commitment to converge religious authority through the spirit of religious moderation while remaining steadfast in their respective orientations. Keywords: Religious Authority, Contestation, The Media, Gender